2019
DOI: 10.15252/emmm.201910697
|View full text |Cite
|
Sign up to set email alerts
|

Role of bulge epidermal stem cells and TSLP signaling in psoriasis

Abstract: Psoriasis is a common inflammatory skin disease involving a cross‐talk between epidermal and immune cells. The role of specific epidermal stem cell populations, including hair follicle stem cells (HF‐SCs) in psoriasis is not well defined. Here, we show reduced expression of c‐JUN and JUNB in bulge HF‐SCs in patients with scalp psoriasis. Using lineage tracing in mouse models of skin inflammation with inducible deletion of c‐Jun and JunB, we found that mutant bulge HF‐SCs initiate epidermal hyperplasia and skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 59 publications
3
25
0
Order By: Relevance
“…Thus, c-Jun and JunB seem to either compensate for each other or cooperate by a currently unclear mechanism. Our data demonstrate for the first time such a non-redundant function for c-Jun and JunB in immune cells, but similar observations have been made in keratinocytes and hair follicle stem cells [ 25 , 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, c-Jun and JunB seem to either compensate for each other or cooperate by a currently unclear mechanism. Our data demonstrate for the first time such a non-redundant function for c-Jun and JunB in immune cells, but similar observations have been made in keratinocytes and hair follicle stem cells [ 25 , 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our data provide evidence that c‐Jun/AP1 has a multi‐faceted, cell‐type specific function in the pathogenesis of psoriasis. The Jun/AP‐1 family plays an important role in the epidermal compartment for the pathogenesis of psoriasis (Gago‐Lopez et al, 2019). JunB, located on the PSOR6 locus, is down‐regulated in psoriatic epidermis (Zenz et al, 2005), whereas c‐Jun expression is up‐regulated in the basal layer with a possible impact on keratinocyte proliferation (Mehic et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although various studies have highlighted the effects of TSLP in the skin DCs activation, its performances in the interaction of epidermal cells have rarely been investigated ( 11 , 29 ). Recent studies have demonstrated TSLP, as an autocrine and paracrine factor, produced mainly by mutant bulge hair follicle stem cells and basal keratinocytes, can stimulate adjacent non-mutant epidermal cells to hyper-proliferate and express vascular endothelial growth factor α, thus contributing to skin inflammation and epidermal hyperplasia in PVs patients ( 74 ). Local injection of TSLP antibodies in the psoriasis-like mouse model led to skin inflammation regression, reduced epidermal hyperplasia, decreased vascular endothelial growth factor α expression, and epidermal inhibition of STAT-5 phosphorylation ( 74 ).…”
Section: Tslp and Cutaneous Immune-mediated Disordersmentioning
confidence: 99%